Principal Leadership in a Time of Change - Corrigan, John; Merry, Mark (Frontiers in Education, 2022)
Education is undergoing a period of sustained change from a focus on traditional skills and compliance to positional authority, to a focus on twenty-first century skills and more adaptable behaviours. In the light of this changing context, this study examined the role of school principalship and identified those attributes which teachers and students recognize as being desirable in a school leader today. Principals come in all shapes and sizes, have different leadership styles, spend time on different things, and are judged on their performance based upon what they say and do, how well their school is performing, and how happy the led are with their leader. The study looked at the various leadership styles emerging from the extensive literature. The statements used in the survey were drawn from six different principal styles, with five attribute statements for each style. Teachers and students (N = 405) across nine schools completed a two-part survey in which they were asked to rank leadership attributes in order of importance. In this way we identified specific attributes deemed desirable in a school leader. The results showed high statistical significance. The findings were quite conclusive: Teachers and students preferred the Integrated Leadership style which combines instructional and transformational leadership and agreed on the importance of principal as role model for both students and colleagues. This key element of the principal’s role was linked to two other attributes, these being that a principal should (a) foster a shared vision in the school, and (b) have a vision for the school that they help to develop with colleagues. These findings give rise to some interesting questions, one being: What does it mean to be a role model in the context of twenty-first century education? A second being, what is the link between shared vision and role modelling?